PENGARUH TINGKAT PENDIDIKAN, PELATIHAN, DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PT. ASURANSI TAKAFUL BATAM - Noviyanti Rianti Putri; Sri Langgeng Ratnasari (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2019)
The purpose of this study was to determine the effect of the level of education on employee performance, the effect of training on employee performance, the influence of career development on employee performance, and the influence on the level of education, training, career development on the performance of employees of PT. Takaful Insurance Batam. This type of research is quantitative descriptive research. The technique of collecting data using a questionnaire. The study population was 50 people with a sample of 50 employees, who were chosen as a whole so that they used saturated sampling. The results of this study indicate that the level of education shows that the level of education does not affect employee performance. Training variable shows that training does not affect employee performance. Career development variable shows that career development has no effect on employee performance. Meanwhile F test results simultaneously shows that education, training, career development has no effect towards employee performance variables.